Indonesia : Financial Sector Assessment Program-Detailed Assessment of Observance-Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2018)
This paper reviews observance of Insurance Core Principles in Indonesia. Insurance regulation and supervision have been remarkably improved since the establishment of the Financial Services Authority (OJK) and the enactment of the new Insurance Law. However, the assessment has identified a significant number of shortfalls in observance with the Insurance Core Principles. Some deficiencies are owing to the lack of effective group regulation and supervision of insurance groups. Although OJK has implemented regulations related with risk management and group capital, intragroup transactions are not well taken into account. It is recommended that OJK should improve the effectiveness of supervision. Thematic reviews of reserving practices will encourage more conservative reserving.